Acquisition enables Saint-Gobain to offer heat-resistant metal seals. Issue 4 (April 2020) - Unknown
Abstract : Saint-Gobain Seals recently acquired a designer and manufacturer of engineered metal seals for the industrial, energy and aerospace markets.